Masalah Emosi dan Perilaku pada Penderita TB Anak - Giri Widakdo; Erni Rita; Indah Noviana Saputri; Tria Astika Endah Permatasari; Ika Kurniaty (STIKes Payung Negeri Pekanbaru, 2020)
One of the effects of emotional and behavioral problems in children with TB is the disruption of productivity and quality of life including children's education.This study aims to identify emotional and behavioral problems in children with TB in the Central Jakarta Health Center and East Jakarta Health Center. The design of this study was cross-sectional in 91 pediatric TB patients in 2019 as measured using the Strength and Dfficulties Questionary (SDQ). The results showed an analysis of the distribution of problem scores and behavior of TB sufferers in children based on covariates, namely: for behavior problems found in the abnormal group both for normal nutritional status (89.4%), history of household contact (57.6%) and TB status negative (80.3%) and for relationships with peers, the largest abnormal group was found in normal nutritional status (92%), family contact history (60%) and negative TB status (84%) and difficulty scores in the abnormal category were in normal nutritional status (89.9%), household contact history (60%) and negative TB status (80%) Conclusion:. The distribution of SDQ scores with covariates (Nutritional Status, Contact History and TB Status), for the abnormal categories are: peer behavior problems and difficulty scores. Parents, teachers or health centers can follow up on SDQ results to anticipate mental health disorders in children